Phragmacossia bozanoi—a new species from southern Greece with some notes on Phragmataecia and Phragmacossia (Lepidoptera, Cossidae, Zeuzerinae) - Saldaitis, Aidas; Prozorov, Alexey M.; Müller, Günter C.; Yakovlev, Roman V. (Zootaxa, 2023)
The taxonomic relationship between the genera Phragmataecia Newman, 1850 and Phragmacossia Schawerda, 1924 is considered. Diagnostic characters and distribution of the species Phragmataecia castaneae (Hübner, 1790), Phragmataecia albida (Erschoff, 1874), Phragmacossia ariana (Grum-Grshimailo, 1899), Phragmacossia territa (Staudinger, 1879), and Phragmacossia minos Reisser, 1963 are studied in detail. A new species, Phragmacossia bozanoi sp. n., is described from the Peloponnese Peninsula and the South Greek mainland.